Menilai kinerja keuangan PT. Sumber Alfaria Trijaya Tbk (Alfamart) periode 2018-2021 dengan menggunakan rasio profitabilitas dan rasio solvabilitas - Dwi Dayanti Oktavia; Alfiah Alfiah; Irma Mugi Lestari (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
The research background is the financial performance of PT. Sumber Alfaria Trijaya as a retail industry which is in tight business competition from other retail companies and online shops. The research objective is to determine the financial performance of PT Sumber Alfaria Trijaya in 2018-2021 through profitability and solvency ratios. The research method used is descriptive quantitative. The research was conducted by analyzing the company's financial statements PT. Alfaria Trijaya sources for the period 2018 – 2021. Data collection techniques are documentation and literature study. The analysis technique used is descriptive analysis of trend analysis of profitability and solvency ratios as well as comparisons with industry standards. The results show that the trend of changes in the profitability ratios has increased with an increasing tendency from 2018 to 2021, while the trend of changes in the solvency ratio has a downward trend from 2018 to 2021. Meanwhile, the trend of changes in the financial performance of PT Sumber Alfaria Trijaya is getting better but not yet sufficient to meet industry standards. The conclusion of the research results is that the financial performance of PT Sumber Alfaria Trijaya has not met industry standards.